Faktor Determinan Inormasi Pengguna Mobile Banking Bank Xyz - Adi Purnama dan Carunia Mulya Firdausy (Universitas Tarumanagara, 2019)
This study aims to examine the effect of usage barrier, value barrier, risk barrier, initial trust, perceived usefulness to information of mobile banking user. The sample used in this research is 105 respondents. Testing is estimated by using multiple linear regression analysis, data hypothesis processed using SPSS program version 21.The results showed that usage barrier negatively affect the information of mobile banking user. While value barrier, risk barrier, initial trust, perceived usefulness positively affect the information of mobile banking user. With this research, it is expected that Bank will improve the mobile banking service which is easily accessed and used by the customers